Alliance formation in a cooperative container shipping game: Performance of a real options investment approach. (May 2017) - Rau, Philipp; Spinler, Stefan
Highlights: Normative model for dynamic alliance composition and investment in shipping. Comparison of real options and discounted cash flow investment models. Real options best for shipping investment, especially if competitive/volatile market. Alliance instability drivers: competition, complexity cost, and freight rate volatility. Abstract: This paper develops an integrated alliance formation and investment simulation model within container shipping. In light of low profitability and frequent alliance changes, the optimal choice of investment approach is addressed. This is achieved by comparing the performance of three investment approaches: real options analysis, and individual and collective discounted cash flow. It turns out that the real options trigger performs best, especially under conditions of high competitive intensity and freight rate volatility. A sensitivity analysis concludes that competitive intensity, alliance complexity cost, and freight rate volatility lead to alliance instability and that shorter lead times increase industry concentration.